Evolution of the Surgical Net - O'Daniel, Thomas G.; Kachare, Milind D. (Facial Plastic Surgery, 2024)
The surgical net technique, originally conceptualized to mitigate postoperative hematomas, has evolved into a versatile tool, transcending its initial purpose, and signaling a new era of surgical innovation. This article provides a comprehensive overview of the surgical net's journey from a targeted solution to a multifaceted surgical asset and explores its burgeoning applications, challenges, and future trajectories. Despite early reluctance due to anatomical concerns and unfamiliarity with the novel technique, the surgical net's consistent success in various surgical contexts from facial surgeries to gynecological applications has catalyzed its widespread global adoption. The technique's integration of the progressive tension method and enhanced skin redraping capabilities underscores its contribution to optimal aesthetic outcomes and improved surgical control. Noteworthy is its role in the innovative concept of gliding surgery, marked by procedures like the gliding brow lift and Glidelift, demonstrating the surgical net's adaptability and effectiveness in diverse surgical environments.Contributions from international surgeons have expanded its applications to areas like axillary space obliteration after breast implant, postmastectomy closure, and the management of postpartum hemorrhage, showcasing the surgical net's global impact and universal commitment to optimizing surgical outcomes. The article delves into the anatomical considerations essential for adapting the surgical net technique to various surgical contexts, emphasizing the need for continuous research, clinical trials, and multidisciplinary collaboration to navigate emerging challenges and ensure its sustained efficacy and safety.In conclusion, the article highlights the surgical net technique's unwavering potential for further advancements, greater procedural efficiency, and the continued elevation of patient care standards. The consistent evolution of its applications, paired with a dedicated approach to addressing emergent challenges, reinforces the surgical net's enduring contribution to surgical innovation and global patient welfare.
Keywords: hemostatic net; surgical net; hemostasis; surgical Innovation